Mission-based online generation of probabilistic monitoring models for mobile robot navigation using Petri nets - Mekacher, Leila; Alexopoulos, Alexander; Wagner, Achim; Badreddin, Essameddin (Robotics and autonomous systems, 2014)
This paper presents a generic hybrid monitoring approach, which allows the detection of inconsistencies in the navigation of autonomous mobile robots using online-generated models.